Faktor Risiko Terjadinya Sudden Cardiac Death - Ishmah Faza Andi; Pratiwi N Hamzah; Sumarni; Indah Lestari Daeng Kanang (Fakumi Medical Journal: Jurnal Mahasiswa Kedokteran, 2023)
Sudden death according to the World Health Organization (WHO) is death that occurs within 24 hours after the onset of symptoms. Sudden death occurs relatively quickly in a person with unknown or unclear causes. Sudden death can be caused by diseases of the heart and blood vessels, diseases of the respiratory system or central nervous system. In the world, heart disease ranks first as a disease that causes death, followed by infectious diseases and cancer. In 2008, an estimated 17.3 million deaths were caused by heart and blood vessel disease. Sudden death due to heart disease is 60% of all cases. These heart and blood vessel diseases include coronary heart disease, myocardial infarction, myocarditis, cardiomyopathy, heart valve disorders, and genetic disorders of the heart. This research method uses the narrative review method based on literature or research that has been conducted and published in accredited international and national journals. The results of this study are that the risk factors for Sudden Cardiac Death vary widely, consisting of risk factors for age, race, gender, heredity, diabetes mellitus, hypertension, alcohol consumption, smoking, obesity, heart disease and abnormal EKG results, hypercholesterolemia, and exercise. certain. Conclusion based on the results of a review of several literatures it can be concluded that there is vary risk factors for Sudden Cardiac Death.